2007
DOI: 10.3141/2002-07
|View full text |Cite
|
Sign up to set email alerts
|

Crosswalk Confusion

Abstract: Traffic safety researchers have long argued that driver behavior outweighs physical elements (such as road design) as a causal factor in motor vehicle collisions. A fundamental causal component of pedestrian-vehicle collisions is also behavior: that of the driver and that of the pedestrian. One determinant of this behavior may be whether the driver, the pedestrian, or both understand the motor vehicle code, which demarcates the right-of-way in pedestrian-vehicle interactions. That is, inappropriate or unlawful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The study result also show that zebra marked crosswalks have lower category of QOS than the nonzebra crosswalk locations because of the increase in pedestrian-vehicle interaction at zebra crosswalk locations due to ambiguity of driver yield behaviour. Early research studies found that marked crosswalks have lower safety than the non-marked crosswalk locations at uncontrolled crosswalk locations (Zegeer et al 2001;Mitman, Ragland 2007). The driver yield behaviour under mixed traffic conditions in developing countries is quite different when compared with developed countries and it is noticed only when the pedestrians are using the crosswalks or when the pedestrians already reached the vehicular lanes (Kadali, Vedagiri 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The study result also show that zebra marked crosswalks have lower category of QOS than the nonzebra crosswalk locations because of the increase in pedestrian-vehicle interaction at zebra crosswalk locations due to ambiguity of driver yield behaviour. Early research studies found that marked crosswalks have lower safety than the non-marked crosswalk locations at uncontrolled crosswalk locations (Zegeer et al 2001;Mitman, Ragland 2007). The driver yield behaviour under mixed traffic conditions in developing countries is quite different when compared with developed countries and it is noticed only when the pedestrians are using the crosswalks or when the pedestrians already reached the vehicular lanes (Kadali, Vedagiri 2013).…”
Section: Discussionmentioning
confidence: 99%
“…and level of separation from driving lanes. Drivers approaching a crosswalk or driving next to a bike lane may not always understand the rules that are applied to a specific configuration or marking ( 11 ). Past studies have used traffic images and network-level videos to examine pedestrian-vehicle interactions ( 12 14 ).…”
mentioning
confidence: 99%